STUDENTS’ DIFFICULTIES IN UNDERSTANDING STATISTICAL CALCULATION - Ihda Ulfah Arismika; Iyan Irdiyansyah; Entis Sutisna (Journal of English Teaching and Linguistics Studies (JET Li), 2021)
The paper entitled “Students’ Difficulties in Understanding Statistical Calculation” is conducted to analyze the students’ difficulty in understanding statistical calculation and the causes of it. The research is applied to the seventh semester students of English Education Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. Students who got low score in statistics subject are chosen as the participants. Descriptive method is used in conducting this research. Questionnaire and interview are used to collect the data of this research. The result of this research shows that the students get difficulties in understanding statistical calculation. The problems are students are not able to answer statistics questions. Additionally, they are not able to understand the statistical formulas, not able to use scientific calculator, and not able to absorb the material that was taught well. Then, the causes are they are not interested in statistical calculation, they are not taught by interesting method, they were weak in calculating, and they are not familiar with scientific calculator.